Tantangan Keberlanjutan Komoditas Lokal: Studi Kasus Emping Melinjo di Desa Dayah Adan, Kabupaten Pidie, Pascabanjir Hidrometeorologi Tahun 2025 - Mujiburrahman Mujiburrahman; Aflia Riski; Ibrahim Chalid; Ade Ihksan Kamil (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
Emping melinjo, a traditional melinjo-based cracker, represents a strategic home-based agro-industrial commodity in Pidie Regency with substantial economic and cultural value. Its sustainability, however, is increasingly threatened by raw-material scarcity resulting from aging melinjo trees, inadequate systematic replanting, limited product innovation, and the 2025 hydrometeorological floods, which destroyed approximately 70% of the local melinjo tree population. This study examines the key challenges affecting the sustainability of emping melinjo production and identifies strategies for strengthening its post-flood resilience. Employing a qualitative case study approach, data were collected through in-depth interviews with farmers and women artisans and complemented by field observations. The findings demonstrate that inadequate tree regeneration and extensive flood damage substantially reduced raw-material availability and production capacity, while reliance on traditional production and marketing practices constrained market competitiveness. The study concludes that sustaining emping melinjo requires an integrated strategy encompassing intensive replanting, targeted cultivation and commercialization, context-sensitive product innovation, premium packaging, and digital marketing to restore production capacity, strengthen market competitiveness, and preserve the commodity’s long-term economic and cultural viability.